2019
DOI: 10.14744/scie.2019.29290
|View full text |Cite
|
Sign up to set email alerts
|

Current Approach to Primary Immunodeficiency Diseases

Abstract: Primary immunodeficiency diseases (PIDD) are inherited disorders resulting from defects in diverse elements of the human immune system. Currently, more than 330 PIDDs have been described, and the molecular (genetic) bases for more than 320 of them are known. PIDD can be divided into nine different groups, including antibody (humoral) deficiencies, innate/intrinsic deficiencies, phagocytic system deficiencies, complement component deficiencies, combined (T and B cells) immunodeficiencies, syndromic combined imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The clinical presentation is highly variable, but most present as recurrent infections, which are common in childhood and therefore may go unnoticed in the primary care setting. 1,2,18 We found that the most frequent group according to the IUIS 2015 classification was predominantly antibody deficiency, which is consistent with the international literature, 1,9 followed by CID with associated or syndromic features and then immunodeficiencies affecting cellular and humoral immunity. LASID announced that it had a registry of 8383 patients with innate errors of the immune system by August 2020, of which 53.2% had a predominantly antibody deficiency.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The clinical presentation is highly variable, but most present as recurrent infections, which are common in childhood and therefore may go unnoticed in the primary care setting. 1,2,18 We found that the most frequent group according to the IUIS 2015 classification was predominantly antibody deficiency, which is consistent with the international literature, 1,9 followed by CID with associated or syndromic features and then immunodeficiencies affecting cellular and humoral immunity. LASID announced that it had a registry of 8383 patients with innate errors of the immune system by August 2020, of which 53.2% had a predominantly antibody deficiency.…”
Section: Discussionsupporting
confidence: 89%
“…Most of them present at an early age as recurrent or severe infections, malignancy, or dysregulation in the immune response; autoinflammation; autoimmunity; or allergic disease. 1,2 In 1970, the World Health Organization created a committee to classify these pathologies. 3 Subsequently, in 2015, the International Union of Immunological Societies Expert Committee for Primary Immunodeficiency (IUIS) modified the classification, given the recent advances of the last 40 years, with the aim to increase awareness, facilitate recognition, standardize nomenclature, standardize the approach, and promote optimal and early treatment for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Initial evaluation in the newborn also includes serum Ig levels. However, measuring quantitative Ig levels (IgG, IgA, IgM, and IgE) are less useful in neonate, because neonates produce only small amount of Igs and most of the IgG in early infancy is transferred IgG from the mothers [ 8 , 10 , 11 , 22 , 23 ].…”
Section: Initial Laboratory Evaluation For Primary Immunodeficiencies Of Newbornmentioning
confidence: 99%